1994
DOI: 10.1111/j.1439-037x.1994.tb00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen, Phosphorus and Potassium Concentrations in Developing Maize Grains

Abstract: A 2‐year (1989, 1990) experiment was conducted in the Carpathian Basin near Keszthely, Hungary to evaluate the course of nitrogen (N), phosphorus (P) and potassium (K) concentrations in the developing grain. Two maize hybrids were grown at four rates of N application (0, 50, 150 and 250 kg N ha‐1). Plots had been fertilized at these levels since 1983. As a result of the long‐term N treatments, stocks of P and K in the soil decreased as the rate of N application increased. As expected, concentrations of N in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 12 publications
5
12
1
Order By: Relevance
“…At maturity, P, K, and S contents in the maize grain were positively affected by the N rate. Similar N rate effects on maize grain N, P, and K were previously documented (Hanway, 1962b;Arnold et al, 1977;Feil et al, 1993;Alfoldi et al, 1994). Two points are noteworthy for all nutrients: (i) shoot nutrient concentrations declined rapidly from the R1 to R3 stages, and (ii) at different ear BM, the ear nutrient concentration displayed a narrow variation range, thus reflecting a conservative feature (similar to the leaf nutrient concentration during the vegetative phase).…”
Section: Plant Components: Phosphorus Potassium and Sulfursupporting
confidence: 79%
“…At maturity, P, K, and S contents in the maize grain were positively affected by the N rate. Similar N rate effects on maize grain N, P, and K were previously documented (Hanway, 1962b;Arnold et al, 1977;Feil et al, 1993;Alfoldi et al, 1994). Two points are noteworthy for all nutrients: (i) shoot nutrient concentrations declined rapidly from the R1 to R3 stages, and (ii) at different ear BM, the ear nutrient concentration displayed a narrow variation range, thus reflecting a conservative feature (similar to the leaf nutrient concentration during the vegetative phase).…”
Section: Plant Components: Phosphorus Potassium and Sulfursupporting
confidence: 79%
“…Kerkhoff et al (2006) reported that flowers and seeds are rich in mitochondria, which have a higher N and P contents. However, the present study showed that P contents were higher in the N0 treatment in both anthesis and harvest stages, consistent with Perring et al (2009) who found that nitrogen fertilizer could decrease plant P contents and suggested that grain P concentrations may be decreased significantly with increasing N addition (Alfoldi et al, 1994;Osborne et al, 2004;Bélanger et al, 2012). These different grain N and P concentration responses to N fertilization could be due to variations in soil N levels .…”
Section: Discussionsupporting
confidence: 67%
“…K concentrations present in ryegrass expressed on both a dry matter and tissue water basis remained within a narrow range irrespective of treatment or time (Jarvis et al 1990). The rate of N application had little impact on the K concentrations in ripe grains (Alfoldi et al 1994). These results show that K concentrations in the grain are well-buffered against increments in grain yield resulting from the application of N and are also relatively insensitive to low supplies of K in the soil (Alfoldi et al 1994).…”
Section: K Uptake and Content In Plants Under Variable N Regimesmentioning
confidence: 84%
“…The rate of N application had little impact on the K concentrations in ripe grains (Alfoldi et al 1994). These results show that K concentrations in the grain are well-buffered against increments in grain yield resulting from the application of N and are also relatively insensitive to low supplies of K in the soil (Alfoldi et al 1994). Contrary to these findings Rui et al (2009) reported that K was significantly lower in treatments with N fertilizer compared to a control without N fertilizer and a significant negative correlation (R) was observed between K and N fertilizer input −0.89.…”
Section: K Uptake and Content In Plants Under Variable N Regimesmentioning
confidence: 84%